MENINGKATKAN SIKAP DEMOKRATIS SISWA DENGAN MODEL PEMBELAJARAN SIMULASI SOSIAL PADA PELAJARAN PKn KONTEKS IPS - Andriani, Ana (JURNAL PENDIDIKAN ILMU SOSIAL, 2013)
This paper is intended to strengthen social studies education especially in citizenship education in developing and increasing students’ democratic attitude through social simulation model. This research is done to expand the students’ awareness of social issues in order to they can play important role as good citizen. Social simulation model is offered as alternative solution to solve the social problem in students’ daily activities in society. The dispute between students group is considered caused by low of students’ awareness of democratic attitude. By developing this model, students can work cooperatively in building social relationship and correspondence, also avoiding solving social problem by anarchies.Key words: citizenship education, students’ democratic attitude, social simulation model.